Susceptibility of knee osteoarthritis patients to develop cardiovascular disease - a clinical study - Sexana, Rahul; Bhattacharya, Ijen; Sexana, Raj (Asian Journal of Medical Sciences, 2013)
Background: Osteoarthritis (OA) is a process of progressive destruction of articular cartilage which makes the OA patients physically inactive and increases the probability to develop cardiovascular disease (CVD). Aim: The objectives of present study were to estimate atherogenic index, markers of oxidative stress and inflammation in knee OA patients of different Kellegren- Lawrence (KL) grade and clarify the probability of knee OA patients to develop future CVD risk with disease severity. Methodology: Atherogenic index, plasma paraoxonase, C-reactive protein (CRP) and erythrocyte malondialdehyde (MDA) levels were estimated by using standard methods in 55 - 70 years aged 76 knee OA patients categorized into three groups (on the basis of KL grading scale) and 24 healthy subjects (control group). The obtained values were compared statistically by using student’s t-test. Result: A significant reduction in the plasma paraoxonase and serum HDL cholesterol levels were observed in (p<0.05) Group II & III knee OA patients. Similarly, erythrocyte MDA, Total cholesterol/HDL ratio and plasma CRP levels were increased significantly in (p<0.05) Group II and III knee OA patients. However, these levels were found to be altered insignificantly (p<0.01) in Group I knee OA subjects as compared to controls. Conclusion: Thus, the probability of KL grade III and IV knee OA patients to develop future risk of CVD are more as characterized by elevated antherogenic index, systemic inflammation and oxidative stress and reflect the need of antioxodants supplementation along with drug of choice to reduce CVD risk in knee OA patients. DOI: http://dx.doi.org/10.3126/ajms.v4i3.8169 Asian Journal of Medical Sciences 4(2013) 62-68